2016
DOI: 10.1093/ajae/aav095
|View full text |Cite
|
Sign up to set email alerts
|

Corn Area Response to Local Ethanol Markets in the United States: A Grid Cell Level Analysis

Abstract: We measure corn and total agricultural area response to the biofuels boom in the United States from 2006 to 2010. Specifically, we use newly available micro‐scale grid cell data to test whether a location's corn and total agricultural cultivation rose in response to the capacity of ethanol refineries in their vicinity. Based on these data, acreage in corn and overall agriculture not only grew in already‐cultivated areas but also expanded into previously uncultivated areas. Acreage in corn and total agriculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…Regardless of the mechanism, the location of an ethanol plant has been shown to be related to local production decisions (i.e., (Miao 2013;Fatal and Thurman 2014;Motamed et al 2016)) and is hence a potentially useful tool to isolate the impact of the ethanol mandate. This includes several periods, 1997(Miao 2013), 2006-2010(Motamed et al 2016), and 2002(Fatal and Thurman 2014, where ethanol plant location has been shown to be related to larger corn production. One plausible hypothesis is that counties with higher ethanol production capacity are likely to see a relatively smaller share of land re-enroll in CRP.…”
Section: Empirical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the mechanism, the location of an ethanol plant has been shown to be related to local production decisions (i.e., (Miao 2013;Fatal and Thurman 2014;Motamed et al 2016)) and is hence a potentially useful tool to isolate the impact of the ethanol mandate. This includes several periods, 1997(Miao 2013), 2006-2010(Motamed et al 2016), and 2002(Fatal and Thurman 2014, where ethanol plant location has been shown to be related to larger corn production. One plausible hypothesis is that counties with higher ethanol production capacity are likely to see a relatively smaller share of land re-enroll in CRP.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Several studies have used ethanol plant location to estimate the impact of ethanol production and related policies on a variety of outcomes related to crop production, including farmland value and land rents (Henderson and Gloy 2009;Blomendahl et al 2011;Towe and Tra 2013;Kropp and Peckham 2015), local grain price (McNew and Griffith 2005), farm size (Tra and Towe 2016), various measures of land use such as area planted to corn, total agricultural area, intensification, and effect of corn-soy rotation (Miao 2013;Arora et al 2016;Motamed et al 2016), and landowners' decision to exit early from CRP and return to farming (Krumel Jr. et al 2015). By decreasing the local basis, or transportation costs to deliver crops to market, ethanol plants make local crop production more profitable.…”
mentioning
confidence: 99%
“…While corn is increasing in North Dakota, soybean is increasing at a higher rate, and in South Dakota, corn has been decreasing or has remained stable for the past two decades. This finding is somewhat surprising given the recent focus on corn prices and ethanol production (e.g., Feng & Babcock, 2010;Motamed et al, 2016). While the increase of overall area of corn planted does equate to an increase in corn production, it appears that soybean is replacing other crops, not corn.…”
Section: Increase In Corn and Soybean Productionmentioning
confidence: 98%
“…A primary driver of this was the 2007 Energy Independence and Security Act (EISA), which revised the 2005 Renewable Fuels Standard to call for a 900% increase in production of renewable fuels, from 4 billion gallons in 2006 to 36 billion gallons by 2022, with up to 21 billion gallons of advanced biofuels (i.e., noncorn starch based; US Congress, ). Some research suggests that the effects of EISA can be seen with greater cropland conversion occurring in closer proximity to ethanol refineries (Miao, ; Motamed et al., ; Otto et al., ; Wright et al., ), though this relationship may be complicated by indirect effects of increased crop prices due to ethanol expansion (Li, Miao, & Khanna, ).…”
Section: Why Are Cropping Patterns Changing?mentioning
confidence: 99%
See 1 more Smart Citation